Pengaruh Disiplin dan Motivasi Kerja Kepala Sekolah dalam Meningkatkan Kualitas Lembaga Pendidikan Islam - Febia Ghina Tsuraya; Hasyim Asy’ari; Siska Maulidya; Ulfa Nur Fajariya (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Agama Islam Nahdlatul Wathan Samawa Sumbawa Besar, 2023)
Currently, there are still many teachers who teach lack motivation, discipline and maximum performance in carrying out their duties. So it has a negative impact on the quality of graduation and the quality of education. This is a big challenge for school principals in their leadership. Therefore this study aims to describe and examine the